2010
DOI: 10.1021/ol101171v
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic SN2′-Selective Substitution of Allylic Chlorides With Arylboronic Esters

Abstract: A copper-catalyzed S(N)2'-selective arylation of allylic chlorides has been achieved using arylboronic esters as nucleophiles. Arylation products were obtained in high yield with a variety of allylic chlorides and arylboronic esters in the presence of a wide range of functional groups. A mechanism is proposed on the basis of the results of stoichiometric experiments and the isolation of the proposed intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…We proposed two possible reaction patterns of this step. In the first reaction pattern, the naphthyl moiety of Int1 acting as a nucleophile, whose C 1 position was activated by gold catalyst, attacks 2 a through a S N 2 pathway that is similar to the reported mechanism of copper‐catalyzed allylation of arylboronates . The transition state of this process is TS1 with an energy barrier of 24.6 kcal mol −1 .…”
Section: Methodssupporting
confidence: 89%
“…We proposed two possible reaction patterns of this step. In the first reaction pattern, the naphthyl moiety of Int1 acting as a nucleophile, whose C 1 position was activated by gold catalyst, attacks 2 a through a S N 2 pathway that is similar to the reported mechanism of copper‐catalyzed allylation of arylboronates . The transition state of this process is TS1 with an energy barrier of 24.6 kcal mol −1 .…”
Section: Methodssupporting
confidence: 89%
“…For example, formation of enantioenriched products via Cu-catalyzed allylic arylations largely relies on the use of Grignard, organozinc, or organoaluminum reagents; 1216 only a limited number of methods allow the use of arylboronates. 1719 …”
mentioning
confidence: 99%
“…[10] In 2010, two research groups independently reported that arylboronic acid esters are competent nucleophiles in coppercatalyzed allylic substitution reactions using achiral catalysts. [11] Based on this precedent, as well as our recent success in the copper-catalyzed asymmetric addition of organoboronates using Mauduit-type chiral N-heterocyclic carbene (NHC) ligands, [12,13] we initially conducted the reaction of cinnamyl phosphate (1 a) with 4-methoxyphenylboronic acid neopentylglycol ester in the presence of CuCl (5 mol %), chiral NHC salt (S)-4 a (5.5 mol %), [12a] and KOtBu (2.0 equiv) in THF at 30 8C (Table 1, entry 1). Under these reaction conditions, the reaction proceeded smoothly to give a 41:59 mixture of the g-substitution product 2 a and the a-substitution product 3 a in 95 % combined yield; the thus obtained 2 a had a moderate ee value of 56 %.…”
mentioning
confidence: 99%